2019
DOI: 10.3390/atmos10010030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dual-Polarimetric Radar Variables and Quantitative Precipitation Estimators for Landfall Typhoons and Squall Lines Based on Disdrometer Data in Southern China

Abstract: Typhoon rainstorms often cause disasters in southern China. Quantitative precipitation estimation (QPE) with the use of polarimetric radar can improve the accuracy of precipitation estimation and enhance typhoon defense ability. On the basis of the observed drop size distribution (DSD) of raindrops, a comparison is conducted among the DSD parameters and the polarimetric radar observation retrieved from DSD in five typhoon and three squall line events that occurred in southern China from 2016 to 2017. A new pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…From the 2-dimensional video disdrometer (2DVD) measurements in eastern China, Chen et al (2017) determined the polarimetric radar variables for typhoons, mei-yu, and squall line precipitations, and they revealed discrete alterations among these weather systems. Over southern China, distinct differences in the rain integral parameters of typhoons and squall lines were perceived by Zhang et al (2019), and they concluded that it is essential to adopt precipitation-specific rainfall estimators. An examination of typhoons and mei-yu season RSDs in Japan affirmed maritime behavior in typhoons and continental behavior in mei-yu rainfall (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From the 2-dimensional video disdrometer (2DVD) measurements in eastern China, Chen et al (2017) determined the polarimetric radar variables for typhoons, mei-yu, and squall line precipitations, and they revealed discrete alterations among these weather systems. Over southern China, distinct differences in the rain integral parameters of typhoons and squall lines were perceived by Zhang et al (2019), and they concluded that it is essential to adopt precipitation-specific rainfall estimators. An examination of typhoons and mei-yu season RSDs in Japan affirmed maritime behavior in typhoons and continental behavior in mei-yu rainfall (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that the tropical cyclone RSDs varied significantly across different climate regions [4][5][6][7][8][9][10]. Most studies focused on typhoons making landfall on the East Asia continent, such as southeast China [7,9,10], which is strongly influenced by a continental climate, and Wen et al [9] found that typhoon raindrops in continental China are smaller and have higher concentrations than those in the Pacific and Atlantic. However, few studies have been conducted on the impacts of typhoons in the midlatitude area around the Japan Islands, which is greatly influenced by the ocean climate.…”
Section: Introductionmentioning
confidence: 99%
“…The polarimetric radar variables computed with the 2DVD for the typhoon, Mei-yu, and squall line precipitations over Easter China showed distinct differences among these precipitation types (Chen et al, 2017). Over south China, distinct differences in rain integral parameters of typhoons and squall lines were noticed by Zhang et al (2019). They concluded that it is crucial to adopt the precipitation specific rainfall estimators.…”
Section: Seasonal Characteristics Of Rsd Bymentioning
confidence: 99%